THE IMPLEMENTATION OF THE REGULATION OF THE MINISTER OF EDUCATION, CULTURE, RESEARCH, AND TECHNOLOGY NUMBER 19 OF 2024 ON TEACHER PROFESSIONAL EDUCATION IN IMPROVING TEACHER COMPETENCE AT SMK SWASTA GBKP KABANJAHE - Barus, Sedar; Jamaluddin, Yanhar; Lubis, Maksum Syahri (Pena Cendekia Insani, 2026)
This study aims to identify and analyze the implementation of the Teacher Professional Education (Pendidikan Profesi Guru/PPG) policy based on the Regulation of the Minister of Education, Culture, Research, and Technology Number 19 of 2024 in improving teacher competence at SMK Swasta GBKP Kabanjahe, Karo Regency. In addition, this study seeks to identify the supporting and inhibiting factors in the implementation of policies related to the development of teacher professionalism. This research is motivated by the existence of a gap between national education policies and their implementation in private schools, particularly with regard to teacher participation in the PPG program and limitations in supporting resources. This study employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using the interactive model proposed by Miles and Huberman. The results indicate that the implementation of the PPG policy has been carried out, but has not yet been optimal. Supporting factors include the commitment of some teachers and school leaders, the existence of clear regulations, and the positive impact of the PPG program on improving teachers’ pedagogical and professional competencies. Meanwhile, inhibiting factors include uneven policy communication, limited financial and technological resources, high teacher workloads, and a complex bureaucratic structure.